Formulasi, Uji Stabilitas Fisik, dan Uji Aktivitas Secara In Vitro Sediaan Spray Antibau Kaki yang Mengandung Ekstrak Etanol Daun Sirih (Piper betle L.) - Iswandana, Raditya; Sihombing, Lidya KM (UI Scholars Hub, 2017)
Betel leaf has long been proven and widely used in Indonesia for its antibacterial activities. Betel leaf 80% ethanolic extract has high compatibility to be made as a widely used pharmaceutical product, including spray. In 2014 American Podiatric Medical Association, studied a significant increase of foot odor prevalence between our citizens. One of the reasons of foot odor is caused by bacteria, mostly by Bacillus subitilis. This study focused on creating a pharmaceutical product with a strong antibacterial that showed minimum bactericidal concentration (MBC) towards bacteria that caused foot odor. Spray product was chosen because of the great pleasant experience for the user. The study tested various concentrations of betel leaf 80% ethanolic extract, to study its antibacterial activity. Furthermore, stability testing towards its physical property on 8-week storage in three different temperature; room temperature (28±2 ºC), high temperature (40±2 ºC), and low temperature (4±2 ºC), was also conducted. All formulae showed great physical stability profile on organoleptic parameters. Betel leaf 80% ethanolic extract, in the Formula 3 showed minimum bactericidal concentration (MBC) in 2 mm area with the Formula that contained ≥ 2 mg/ml ethanolic extract.